2009
DOI: 10.1186/1746-6148-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the glutathione metabolism could be implicated in the ischemia-induced small intestinal cell damage in horses

Abstract: Background: Colic could be accompanied by changes in the morphology and physiology of organs and tissues, such as the intestine. This process might be, at least in part, due to the accumulation of oxidative damage induced by reactive oxygen (ROS) and reactive nitrogen species (RNS), secondary to intestinal ischemia. Glutathione (GSH), being the major intracellular thiol, provides protection against oxidative injury. The aim of this study was to investigate whether ischemiainduced intestinal injury could be rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This leads to an increase in intracellular calcium levels, initiates anaerobic glycolysis, and activates xanthine oxidase and cell death [1]. In horses, it has been demonstrated that part of this damage after intestinal ischemia is due to alterations in glutathione and S-adenosyl methionine [2]. Recovery of sufficient perfusion may facilitate correction of these changes.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to an increase in intracellular calcium levels, initiates anaerobic glycolysis, and activates xanthine oxidase and cell death [1]. In horses, it has been demonstrated that part of this damage after intestinal ischemia is due to alterations in glutathione and S-adenosyl methionine [2]. Recovery of sufficient perfusion may facilitate correction of these changes.…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings of Marañón et al . [ 19 ], the ischemic intestine releases proinflammatory molecules into the portal and systemic circulation, including hydrogen peroxide, superoxide radicals, cytokines, and arachidonic acid metabolites, causing direct tissue damage and increasing oxidative stress biomarkers. Zuluaga et al demonstrated that 96 hr after inducing gastric mucosal injury in horses, the average plasma concentration of MDA increases [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the moralities due to colic are associated with circulatory collapse due to the absorption of bacterial lipopolysaccharide after a series of events such as ischemic gut injury and rapid degeneration of the intestinal barrier [ 13 ]. Intestinal ischemia as a consequence of colic may lead to the accumulation of harmful oxidative nitrogen and oxygen products [ 19 ]. Assessment of oxidative stress markers may be a useful therapeutic target and a prognostic indicator in several conditions in horses, such as orthopedic-related conditions, Cushing’s syndrome, endometritis, and gastrointestinal diseases [ 21 ].…”
mentioning
confidence: 99%
“…Thus, this suggests that the limiting level of RSNO, DNIC or B-DNIC in horse serum is 200–300 nM. It was shown that with colic of the gastrointestinal tract the level of the main cellular antioxidant glutathione decreases, which may lead to an increase in the role of hemoglobin in NO metabolism [ 39 ]. Thus, our data on the reduction of nitrite in serum may indicate a decrease in the both transport and regulatory forms of NO: RSNO, DNIC or B-DNIC in the serum of horses.…”
Section: Discussionmentioning
confidence: 99%